2021
DOI: 10.1128/mbio.02007-21
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Clinical Microbiome Studies in Urolithiasis Reveal Age, Stone Composition, and Study Location as the Predominant Factors in Urolithiasis-Associated Microbiome Composition

Abstract: Studies focused on the microbiome broadly support the hypothesis that the microbiome influences the onset of chronic diseases such as urinary stone disease. However, it is unclear what environmental factors shape the microbiome in ways that increase the risk for chronic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…Consistent with their reports, we found that E. coli also accounted for a greater proportion of the microbiomes in nephrolithiasis patients than in healthy individuals. Additionally, previous studies have determined that the genus Staphylococcus was overrepresented, while Lactobacillus was less abundant in nephrolithiasis patients than in healthy controls ( Zampini et al., 2019 ; Liu et al., 2020a ; Kachroo et al., 2021 ); again, our findings support these reports. It has been shown that Staphylococcus promotes the formation of kidney stones by producing the enzyme urease, which increases pH, while Lactobacilli exerts an inhibitory action by degrading oxalate ( Lewanika et al., 2007 ; Torzewska et al., 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with their reports, we found that E. coli also accounted for a greater proportion of the microbiomes in nephrolithiasis patients than in healthy individuals. Additionally, previous studies have determined that the genus Staphylococcus was overrepresented, while Lactobacillus was less abundant in nephrolithiasis patients than in healthy controls ( Zampini et al., 2019 ; Liu et al., 2020a ; Kachroo et al., 2021 ); again, our findings support these reports. It has been shown that Staphylococcus promotes the formation of kidney stones by producing the enzyme urease, which increases pH, while Lactobacilli exerts an inhibitory action by degrading oxalate ( Lewanika et al., 2007 ; Torzewska et al., 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…More recently, distinct shifts in the diversity and composition of the urinary and urogenital microbiomes were observed in human urolith formers 9,10,18 . In fact, a comprehensive analysis of the gut and urogenital microbiomes determined that the urogenital microbiome exhibited more pronounced alterations by urolith status than did the gut microbiome 9 .…”
Section: Introductionmentioning
confidence: 99%
“…17 More recently, distinct shifts in the diversity and composition of the urinary and urogenital microbiomes were observed in human urolith formers. 9,10,18 In fact, a comprehensive analysis of the gut and urogenital microbiomes determined that the urogenital microbiome exhibited more pronounced alterations by urolith status than did the gut microbiome. 9 Microbial communities also recently have been identified in the urine of healthy dogs, [19][20][21] but the role of these microbes in CaOx formation in dogs is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…There are many hypotheses but none are definitive. The incidence of urinary stones is related to age, gender, race, dietary habits, genetics, and metabolism ( Sayer, 2017 ; Taguchi et al., 2017 ; Jung et al., 2018 ; Kachroo et al., 2021 ). Urinary stones are also closely associated with microbial taxa ( Dornbier et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%